Thesaurus and Information Retrieval - Kuku, David (My University, 2023)
Information organization and retrieval are the main discussions in this article. The author concentrated on the tool considered one of the oldest in the the area of information retrieval, Thesaurus. Consequently, the author discussed the historical perspective of Thesaurus and its evolution to the present era longside its forma and types.
Keywords: Information; Retrieval; Thesaurus